Titanium alloy implant and preparation method and application thereof

CN117339005BActive Publication Date: 2026-10-27FOURTH MILITARY MEDICAL UNIVERSITY
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202311217449.9
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-09-20
Publication Date
2026-10-27
Estimated Expiration
2043-09-20

AI Technical Summary

Technical Problem

[0004]本发明提供了一种钛合金植入物及其制备方法与应用,有效解决了现有的钛合金植入物导致局部组织过高炎症状态,从而造成钛合金植入物松动和失效的技术问题,同时提供了一种促进局部促炎巨噬细胞向促修复的巨噬细胞转变,加快促炎的局部组织微环境向促修复的微环境转变且促进“钛骨”界面的骨再生的钛合金植入物

Benefits of technology

(0)本发明提供的一种钛合金植入物及其制备方法与应用,本发明通过在钛合金表面构建聚酰胺-胺型树枝状高分子材料包覆的黑磷纳米片(BP@PAMAM)的涂层,得到能够定向吸附促炎因子并促进骨再生的钛合金植入物;将所述钛合金植入物植入人体后,由于大部分促炎因子带负电荷,而改性后的钛合金植入物表面带正电荷的特点,通过正负电相吸引的办法,吸附局部组织微环境中的促炎因子,从而减轻局部过高的炎症状态,促进局部促炎巨噬细胞向促修复的巨噬细胞转变,从而使局部早期变成一个促修复的微环境,有利于“钛骨”界面的骨再生。另外,本发明制备的钛合金植入物于局部组织微环境中逐渐释放磷酸根离子,提高了植入后“钛-骨”界面成骨细胞细胞活力,从而提升了钛合金内植物骨整合的效果。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN117339005B_ABST
    Figure CN117339005B_ABST
Patent Text Reader

Abstract

The application discloses a titanium alloy implant and a preparation method and application thereof, and belongs to the technical field of titanium alloy materials. The titanium alloy implant is obtained by constructing a coating of polyamide-amine dendritic polymer material coated black phosphorus nanosheet on the surface of the titanium alloy, and the coating can be used for directional adsorption of proinflammatory factors and promotion of bone regeneration. Since most of the proinflammatory factors are negatively charged, and the surface of the modified titanium alloy implant is positively charged, the proinflammatory factors in the local tissue microenvironment are adsorbed through the method of positive and negative electricity attraction, so that the local excessive inflammatory state is reduced, the local proinflammatory macrophages are converted into pro-repair macrophages, the local early stage becomes a pro-repair microenvironment, and the bone regeneration of a "titanium-bone" interface is facilitated. In addition, the titanium alloy implant prepared by the application gradually releases phosphate ions in the local tissue microenvironment, improves the cell activity of osteoblasts at the "titanium-bone" interface after implantation, and thus improves the effect of bone integration of the titanium alloy implant.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of titanium alloy materials technology, specifically to a titanium alloy implant, its preparation method, and its application. Background Technology

[0002] Titanium alloy implants are currently the most commonly used implants in orthopedic clinics. However, after implantation, local tissues and cells are damaged, leading to a significant increase in levels of local injury-related molecular patterns, including free DNA, lipopolysaccharides, and various pro-inflammatory cytokines, resulting in a high level of inflammation in the local area. Under these conditions, bone regeneration at the titanium-bone interface is hindered, greatly increasing the risk of implant loosening and failure. If implant loosening or failure occurs, a second surgery is generally required, which places a significant physical and financial burden on the patient.

[0003] To overcome the problems arising after implantation of titanium alloy implants, researchers have modified the titanium alloy coating, focusing primarily on promoting osteogenic function of osteoblasts or bone marrow mesenchymal stem cells, thereby facilitating osseointegration at the "titanium-bone" interface. However, the early local microenvironment after implantation directly determines the osteogenic activity of osteoblasts or bone marrow mesenchymal stem cells in the mid-to-late stages. An excessively inflammatory microenvironment in the early stages is highly detrimental to bone regeneration in the mid-to-late stages. Effectively improving the excessively inflammatory state of local tissues after titanium alloy implantation, thereby promoting osseointegration at the "titanium-bone" interface, is a crucial problem that urgently needs to be solved. Therefore, this invention provides a titanium alloy implant, its preparation method, and its applications. Summary of the Invention

[0004] This invention provides a titanium alloy implant, its preparation method, and its application, effectively solving the technical problem that existing titanium alloy implants cause excessive inflammation in local tissues, leading to loosening and failure of the implants. It also provides a titanium alloy implant that promotes the transformation of local pro-inflammatory macrophages into pro-repair macrophages, accelerates the transformation of the pro-inflammatory local tissue microenvironment into a pro-repair microenvironment, and promotes bone regeneration at the "titanium-bone" interface.

[0005] The first objective of this invention is to provide a method for preparing a titanium alloy implant, characterized by comprising the following steps: S1, black phosphorus nanosheets (BP) and polyamide-amine dendritic polymer (PAMAM) were mixed in deionized water, stirred in the dark at room temperature, centrifuged, and the supernatant was discarded to obtain the precipitate. The precipitate was washed to obtain a suspension of black phosphorus nanosheets coated with polyamide-amine dendritic polymer (BP@PAMAM). The titanium alloy was placed in a tannic acid solution and soaked for 24 hours, then rinsed with deionized water to obtain a tannic acid-coated titanium alloy. S2, the tannic acid-coated titanium alloy of S1 was placed in a suspension of black phosphorus nanosheets coated with polyamide-amine dendritic polymer material and soaked for 2 hours to obtain a titanium alloy implant coated with BP@PAMAM.

[0006] Preferably, in S1, the concentration of black phosphorus nanosheets in the black phosphorus nanosheet suspension coated with the polyamide-amine dendritic polymer material is 1~2 mg / mL.

[0007] Preferably, in S1, the concentration of the polyamide-amine dendritic polymer material in the black phosphorus nanosheet suspension coated with the polyamide-amine dendritic polymer material is 10~15 mg / mL.

[0008] Preferably, in S1, the mass concentration of the tannic acid solution is 1~2 mg / mL.

[0009] Preferably, in S1, the ratio of the titanium alloy to the tannic acid solution is 1g:5~10mL.

[0010] Preferably, in S2, the black phosphorus nanosheets coated with polyamide-amine dendritic polymer material account for 30% to 40% of the mass of the titanium alloy implant.

[0011] The second objective of this invention is to provide an application of the titanium alloy implant prepared by the above-described method in the preparation of various titanium metal medical devices used in the clinical medical field.

[0012] Preferably, the titanium alloy implant is used in the manufacture of orthopedic titanium metal medical devices.

[0013] Compared with the prior art, the beneficial effects of the present invention are as follows: (0) This invention provides a titanium alloy implant, its preparation method, and its application. This invention obtains a titanium alloy implant capable of directionally adsorbing pro-inflammatory factors and promoting bone regeneration by constructing a coating of black phosphorus nanosheets (BP@PAMAM) on the surface of a titanium alloy using a polyamide-amine dendritic polymer material. After implantation, the titanium alloy implant, due to the negative charge of most pro-inflammatory factors and the positive charge on the surface of the modified titanium alloy implant, adsorbs pro-inflammatory factors in the local tissue microenvironment through the attraction of positive and negative charges. This alleviates excessive local inflammation and promotes the transformation of local pro-inflammatory macrophages into pro-repair macrophages, thus creating a pro-repair microenvironment in the early stages, which is beneficial for bone regeneration at the "titanium-bone" interface. Furthermore, the titanium alloy implant prepared in this invention gradually releases phosphate ions in the local tissue microenvironment, increasing the activity of osteoblasts at the "titanium-bone" interface after implantation, thereby enhancing the integration effect of the implant into the bone within the titanium alloy.

[0014] (0) The titanium alloy implant prepared by the present invention has no toxic reaction to the human body after being implanted and has good biocompatibility. Attached Figure Description

[0015] Figure 1 These are scanning electron microscope images of the titanium alloy implant with BP@PAMAM coating in Example 1 of the present invention and the pure titanium sheet implant in Comparative Example 1. Figure 2 The figures show the residual inflammatory factors of the titanium alloy implant with BP@PAMAM coating in Example 1 and the pure titanium sheet implant in Comparative Example 1 after immersion in different inflammatory factor solutions for 1 hour; where Figure A shows the IL-1β inflammatory factor solution with a concentration of 1 ng / ml; Figure B shows the TNF-α inflammatory factor solution with a concentration of 1 ng / ml; and Figure C shows the LPS inflammatory factor solution with a concentration of 10 ng / ml; **P < 0.01; Figure 3 The images show staining of surviving and dead cells after macrophages of the present invention were cultured for 3 days on the surfaces of the titanium alloy implant coated with BP@PAMAM in Example 1 and the pure titanium sheet implant in Comparative Example 1, respectively. Green represents surviving cells and red represents dead cells. Figure 4 The graph shows the expression of macrophage-related genes INOS and CD206 3 days after macrophages were seeded on the surface of the titanium alloy implant coated with BP@PAMAM in Example 1 and the pure titanium sheet implant in Comparative Example 1. **P<0.01; Figure 5 The graph shows the expression of osteogenic genes RUNX2 and OPN 3 days after rat mesenchymal stem cells were inoculated on the surface of the titanium alloy implant coated with BP@PAMAM in Example 1 and the pure titanium sheet implant in Comparative Example 1. **P<0.01. Detailed Implementation

[0016] To enable those skilled in the art to better understand and implement the technical solutions of this invention, the invention will be further described below with reference to specific embodiments and accompanying drawings. However, the embodiments described are not intended to limit the invention. Unless otherwise specified, the following test methods and detection methods are conventional methods; unless otherwise specified, the reagents and raw materials are commercially available.

[0017] Example 1 A method for preparing a titanium alloy implant includes the following steps: S1, black phosphorus nanosheets (BP) and polyamide-amine dendritic polymer (PAMAM) were mixed in deionized water, stirred in the dark at room temperature, centrifuged, and the supernatant was discarded to obtain a precipitate. The precipitate was washed to obtain a black phosphorus nanosheet suspension coated with polyamide-amine dendritic polymer (BP@PAMAM); wherein the concentration of black phosphorus nanosheets was 1 mg / mL and the concentration of polyamide-amine dendritic polymer was 10 mg / mL; The titanium alloy was placed in a tannic acid solution with a mass concentration of 1 mg / mL at a dosage ratio of 1 g: 5 mL and soaked for 24 h. It was then rinsed with deionized water to obtain a titanium alloy coated with tannic acid. S2, the tannic acid-coated titanium alloy of S1 is placed in a solution of black phosphorus nanosheets coated with polyamide-amine dendritic polymer material and soaked for 2 hours to obtain a titanium alloy implant coated with BP@PAMAM. In the titanium alloy implant, the black phosphorus nanosheets coated with polyamide-amine dendritic polymer material account for 35% of the mass of the titanium alloy.

[0018] Example 2 A method for preparing a titanium alloy implant includes the following steps: S1, black phosphorus nanosheets (BP) and polyamide-amine dendritic polymer (PAMAM) were mixed in deionized water, stirred in the dark at room temperature, centrifuged, and the supernatant was discarded to obtain a precipitate. The precipitate was washed to obtain a black phosphorus nanosheet suspension coated with polyamide-amine dendritic polymer (BP@PAMAM); wherein the concentration of black phosphorus nanosheets was 2 mg / mL and the concentration of polyamide-amine dendritic polymer was 15 mg / mL; The titanium alloy was placed in a tannic acid solution with a mass concentration of 2 mg / mL at a dosage ratio of 1 g: 10 mL and soaked for 24 h. It was then rinsed with deionized water to obtain a titanium alloy coated with tannic acid. S2, the tannic acid-coated titanium alloy of S1 is placed in a solution of black phosphorus nanosheets coated with polyamide-amine dendritic polymer material and soaked for 2 hours to obtain a titanium alloy implant coated with BP@PAMAM. In the titanium alloy implant, the black phosphorus nanosheets coated with polyamide-amine dendritic polymer material account for 30% of the mass of the titanium alloy.

[0019] Example 3 A method for preparing a titanium alloy implant includes the following steps: S1, black phosphorus nanosheets (BP) and polyamide-amine dendritic polymer (PAMAM) were mixed in deionized water, stirred in the dark at room temperature, centrifuged, and the supernatant was discarded to obtain a precipitate. The precipitate was washed to obtain a black phosphorus nanosheet suspension coated with polyamide-amine dendritic polymer (BP@PAMAM); wherein the concentration of black phosphorus nanosheets was 1.5 mg / mL and the concentration of polyamide-amine dendritic polymer was 12 mg / mL. The titanium alloy was placed in a tannic acid solution with a mass concentration of 1.5 mg / mL at a dosage ratio of 1 g: 8 mL and soaked for 24 h. It was then rinsed with deionized water to obtain a titanium alloy coated with tannic acid. S2, the tannic acid-coated titanium alloy of S1 is placed in a solution of black phosphorus nanosheets coated with polyamide-amine dendritic polymer material and soaked for 2 hours to obtain a titanium alloy implant coated with BP@PAMAM. In the titanium alloy implant, the black phosphorus nanosheets coated with polyamide-amine dendritic polymer material account for 40% of the mass of the titanium alloy.

[0020] Example 4 A method for preparing a titanium alloy implant includes the following steps: S1, black phosphorus nanosheets (BP) and polyamide-amine dendritic polymer (PAMAM) were mixed in deionized water, stirred in the dark at room temperature, centrifuged, and the supernatant was discarded to obtain a precipitate. The precipitate was washed to obtain a black phosphorus nanosheet suspension coated with polyamide-amine dendritic polymer (BP@PAMAM); wherein the concentration of black phosphorus nanosheets was 1 mg / mL and the concentration of polyamide-amine dendritic polymer was 15 mg / mL. The titanium alloy was placed in a tannic acid solution with a mass concentration of 2 mg / mL at a dosage ratio of 1 g: 10 mL and soaked for 24 h. It was then rinsed with deionized water to obtain a titanium alloy coated with tannic acid. S2, the tannic acid-coated titanium alloy of S1 is placed in a solution of black phosphorus nanosheets coated with polyamide-amine dendritic polymer material and soaked for 2 hours to obtain a titanium alloy implant coated with BP@PAMAM. In the titanium alloy implant, the black phosphorus nanosheets coated with polyamide-amine dendritic polymer material account for 30% of the mass of the titanium alloy.

[0021] To further illustrate the technical effects of the present invention, comparative examples are also provided, as follows: Comparative Example 1 The difference compared to Example 1 is that it uses a pure titanium implant.

[0022] Scanning electron microscopy (SEM) images of the titanium alloy implant coated with BP@PAMAM prepared in Example 1 of this invention and the pure titanium sheet implant in Comparative Example 1 are shown below. Figure 1 As shown in Table 1, the distribution of EDS elements is as follows.

[0023] Table 1. Elemental distribution of the titanium alloy implant coated with BP@PAMAM in Example 1 of the present invention. C 49.37 64.64 O 22.65 22.28 N 3.70 4.16 P 5.21 2.65 Ti 19.07 6.27 Depend on Figure 1 It can be seen that the BP@PAMAM coating on the titanium alloy implant of Example 1 of the present invention is uniformly grafted onto the surface of the titanium sheet; according to the calculation of N atoms and P atoms in Table 1, the mass content of BP@PAMAM coating on the surface of the titanium alloy implant prepared in Example 1 of the present invention is about 35%.

[0024] The residual inflammatory factors of the titanium alloy implant coated with BP@PAMAM in Example 1 and the pure titanium sheet implant in Comparative Example 1 after immersion in different inflammatory factor solutions for 1 hour are as follows: Figure 2 As shown, Figure A is a solution of IL-1β inflammatory factor with a concentration of 1 ng / ml; Figure B is a solution of TNF-α inflammatory factor with a concentration of 1 ng / ml; and Figure C is a solution of LPS inflammatory factor with a concentration of 10 ng / ml.

[0025] Ordinary titanium sheets (Comparative Example 1) and titanium alloy implants coated with BP@PAMAM (BP@PAMAM-Ti in Example 1), with a diameter of 10 mm and a height of 2 mm, were selected. Both groups of titanium sheets were sterilized in ethylene oxide at low temperature and placed in 12-well plates, with three replicates for each group. 1 mL of 1 ng / mL IL-1β solution, 1 ng / mL TNF-α solution, and 10 ng / mL LPS solution were added to the wells, respectively. After incubation at room temperature for 1 h, the solutions were aspirated. The concentrations of IL-1β, TNF-α, and LPS in the aspirated solutions were detected using ELISA, and their concentration changes were observed. Figure 2 The results showed that, compared with the original solution, the concentrations of various inflammatory factors in each solution of the BP@PAMAM titanium alloy implant of Example 1 of the present invention decreased significantly after immersion. Therefore, the BP@PAMAM titanium alloy implant of Example 1 of the present invention exhibits good adsorption performance for inflammatory factors.

[0026] The biocompatibility experiment of the titanium alloy implant of the present invention, comparing the surviving and dead cells after 3 days of inoculation of macrophages on the surface of the titanium alloy implant coated with BP@PAMAM in Example 1 and the pure titanium sheet implant in Comparative Example 1, is as follows: Figure 3 As shown, green represents living cells and red represents dead cells.

[0027] This study used macrophages (RAW 264.7) as experimental cells, but it is not limited to RAW 264.7; various cell types from other species are also suitable for this study. Ordinary titanium sheets (Comparative Example 1) and titanium alloy implants encapsulating BP@PAMAM (BP@PAMAM-Ti from Example 1) were selected, with a diameter of 10 mm and a height of 2 mm. Both groups of titanium sheets were sterilized in ethylene oxide at low temperature and placed in 24-well plates, with 3 replicates per group. RAW 264.7 cell suspension (10... 5 500 μl of the solution (per ml) was seeded onto each well of the aforementioned titanium plates and incubated at 37°C for 24 h. The cells were then washed three times with sterile PBS. Subsequently, staining was performed using a cell viability / death assay kit (Shanghai Beyotime), and observation was conducted under a fluorescence microscope. Calcein fluoresced to green fluorescence in viable cells, while propidium iodide fluoresced to red fluorescence in dead cells. Figure 3 It can be seen that the titanium alloy implant with BP@PAMAM coating in Example 1 of the present invention can maintain the activity of RAW 264.7 compared with the pure titanium sheet implant in Comparative Example 1, demonstrating good biocompatibility.

[0028] The expression of macrophage-related genes INOS and CD206 on the surfaces of the titanium alloy implant coated with BP@PAMAM in Example 1 and the pure titanium sheet implant in Comparative Example 1, 3 days after inoculation with macrophages, is as follows: Figure 4 As shown.

[0029] Ordinary titanium sheets (Comparative Example 1) and titanium alloy implants encapsulating BP@PAMAM (BP@PAMAM-Ti from Example 1) were selected, with a diameter of 10 mm and a height of 2 mm. Both sets of titanium sheets were sterilized in ethylene oxide at low temperature and placed in 24-well plates, with 3 replicates per set. RAW 264.7 cell suspension (10... 5 The macrophages were seeded at a rate of 500 μl / ml onto each well of titanium discs in the above groups. After incubation at 37°C for 3 days, the discs were washed three times with sterile PBS. RNA was extracted from the cells using the Trizol method, and the expression of macrophage polarization-related genes INOS and CD206 was detected by qPCR.

[0030] Depend on Figure 4It can be seen that the titanium alloy implant with BP@PAMAM coating in Example 1 of the present invention can significantly inhibit the expression of INOS (pro-inflammatory macrophages) and enhance the expression of CD206 (pro-repair macrophages) compared with the pure titanium sheet implant in Comparative Example 1, demonstrating a good ability to promote macrophage polarization into pro-repair macrophages.

[0031] The expression of osteogenic genes RUNX2 and OPN on the surfaces of the titanium alloy implant coated with BP@PAMAM in Example 1 and the pure titanium sheet implant in Comparative Example 1 after 3 days of inoculation with rat mesenchymal stem cells are as follows: Figure 5 As shown.

[0032] Ordinary titanium sheets (Comparative Example 1) and titanium alloy implants encapsulating BP@PAMAM (BP@PAMAM-Ti from Example 1) were selected, with a diameter of 10 mm and a height of 2 mm. Both groups of titanium sheets were sterilized in ethylene oxide at low temperature and placed in 24-well plates, with 3 replicates per group. Rat bone marrow mesenchymal stem cell suspension (10... 5 Cellular RNA was seeded at 500 μl per well onto each of the above-mentioned titanium plates. After incubation at 37°C for 3 days, the cells were washed three times with sterile PBS. RNA was extracted from the cells using the Trizol method, and the expression of osteogenic-related genes RUNX2 and OPN was detected by qPCR.

[0033] Depend on Figure 5 It can be seen that the titanium alloy implant with BP@PAMAM coating in Example 1 of the present invention can significantly promote the expression of osteogenic related genes RUNX2 and OPN compared with the pure titanium sheet implant in Comparative Example 1, and shows good bone regeneration ability.

[0034] Obviously, those skilled in the art can make various modifications and variations to this invention without departing from its spirit and scope. Therefore, if these modifications and variations fall within the scope of the claims of this invention and their equivalents, this invention also intends to include these modifications and variations.

Claims

1. A method for preparing a titanium alloy implant, characterized in that, Includes the following steps: S1, black phosphorus nanosheets and polyamide-amine dendritic polymer are mixed in deionized water, stirred in the dark at room temperature, centrifuged, the supernatant is discarded, the precipitate is washed, and a suspension of black phosphorus nanosheets coated with polyamide-amine dendritic polymer is obtained. The titanium alloy was placed in a tannic acid solution and soaked for 24 hours, then rinsed with deionized water to obtain a tannic acid-coated titanium alloy. In the black phosphorus nanosheet suspension coated with the polyamide-amine dendritic polymer material, the concentration of black phosphorus nanosheets is 1~2 mg / mL; In the black phosphorus nanosheet suspension coated with the polyamide-amine dendritic polymer, the concentration of the polyamide-amine dendritic polymer is 10~15 mg / mL; The mass concentration of the tannic acid solution is 1~2 mg / mL; The ratio of titanium alloy to tannic acid solution is 1g:5~10mL. S2, the tannic acid-coated titanium alloy of S1 is placed in a suspension of black phosphorus nanosheets coated with polyamide-amine dendritic polymer material and soaked for 2 hours to obtain a titanium alloy implant; in the titanium alloy implant, the black phosphorus nanosheets coated with polyamide-amine dendritic polymer material account for 30% to 40% of the mass of the titanium alloy.

2. A titanium alloy implant prepared by the preparation method of claim 1.

3. The application of the titanium alloy implant according to claim 2 in the manufacture of titanium metal medical devices.

4. The application according to claim 3, characterized in that, The application of the titanium alloy implant in the manufacture of orthopedic titanium metal medical devices.

Citation Information

Patent Citations

  • Method for forming albumen layer by mediating albumin on surface of material, biological material and application thereof

    CN109925540A

  • Means and methods for providing a substrate with a biocidal coating, and coated substrates obtainable thereby

    US20220257837A1